Evaluation of Drug Prescribing Practices Based on World Health Organization (WHO) Indicators at Tapian Dolok Community Health Center, Simalungun Regency, in 2025 - Winda Sinaga; Dinawanti Sijabat; Piter Silaban (Benih : Journal of Midwifery, 2025)
Rational drug use through prescription is crucial in healthcare services to ensure patient therapeutic outcomes. Prescribing indicators and complementary indicators from the World Health Organization (WHO) can be used to assess irrational drug use. This study aims to describe the pattern and profile of drug prescribing based on WHO prescribing indicators at the Tapian Dolok Community Health Center in Simalungun Regency. The purpose of this study was to describe drug prescribing during the period January-March 2025 at the Tapian Dolok Community Health Center, Simalungun Regency, based on WHO Prescribing Indicators. The method used in this study was a descriptive observational study with a cross-sectional design. The data used were retrospective data in the form of medical records and 150 patient prescriptions at the Tapian Dolok Community Health Center, Simalungun Regency, during the period January-March 2025. The results of the study showed that the total number of drugs used during the period January-March 2025 at Tapian Dolok Community Health Center, Simalungun Regency was 593 items with an average number of drug items per prescription sheet being 3.9%. The percentage of drug items prescribed with generic names was 100%. The percentage of drug prescriptions with antibiotics was 41.33%. The percentage of drug prescriptions with injection preparations was 0%. The percentage of drug items prescribed in accordance with the National Formulary was 100%..